2020
DOI: 10.1017/s1368980020002402
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and health implications of the dietary transition among Inuit in the Canadian Arctic: a scoping review

Abstract: Objective: The current study undertook a systematic scoping review on the drivers and implications of dietary changes among Inuit in the Canadian Arctic. Design: A keyword search of peer-reviewed articles was performed using PubMed, Web of Science, CINAHL, Academic Search Premier, Circumpolar Health Bibliographic Database and High North Research Documents. Eligibility criteria included all full-text articles of any design reporting on research on food consumption, nutrient intake, dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 187 publications
(384 reference statements)
0
44
0
Order By: Relevance
“…Dietary studies have reported that while country food contributed a low percentage to total energy intake, country food intake was associated with improved nutrient intake in adults [ 2 , 6 , 28 , 29 , 31 , 34 , 35 ]; furthermore, regular consumers of country food had higher intake of key micronutrients (including n-3 fatty acids, vitamins A, B 6 , B 12 , D, E) and lower intakes of carbohydrate, saturated fat, and sodium [ 36 ]. Country food has also been associated with a higher intake of protein and micronutrients, such as vitamin D and iron, that, when deficient, have been associated with conditions such as rickets and iron-deficiency anemia in Inuit children [ 37 , 38 , 39 , 40 ] highlighting the importance and potential of country food to help address nutrition-related health conditions among Inuit [ 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary studies have reported that while country food contributed a low percentage to total energy intake, country food intake was associated with improved nutrient intake in adults [ 2 , 6 , 28 , 29 , 31 , 34 , 35 ]; furthermore, regular consumers of country food had higher intake of key micronutrients (including n-3 fatty acids, vitamins A, B 6 , B 12 , D, E) and lower intakes of carbohydrate, saturated fat, and sodium [ 36 ]. Country food has also been associated with a higher intake of protein and micronutrients, such as vitamin D and iron, that, when deficient, have been associated with conditions such as rickets and iron-deficiency anemia in Inuit children [ 37 , 38 , 39 , 40 ] highlighting the importance and potential of country food to help address nutrition-related health conditions among Inuit [ 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Country food has also been associated with a higher intake of protein and micronutrients, such as vitamin D and iron, that, when deficient, have been associated with conditions such as rickets and iron-deficiency anemia in Inuit children [ 37 , 38 , 39 , 40 ] highlighting the importance and potential of country food to help address nutrition-related health conditions among Inuit [ 40 , 41 , 42 ]. While the role of country food and impacts of nutrition transition on Inuit health has been explored [ 36 ], the state of research regarding the role of country food during pregnancy and early human life is less clear. Given that country food is a culturally appropriate and local food source for Inuit communities, and given the critical role of nutrition in pregnancy and early human life for immediate and long-term health, the objective of this scoping review was to systematically map published literature and explore the nature, extent, and range of research activity related to the role of country food in pregnancy and early childhood on health among Circumpolar Inuit.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is particularly worrying seeing that Cryptosporidium infection (with or without diarrhea) has been associated with reduced linear growth, lower adult height, impaired cognitive development, poor performance in school, and less economic productivity [78][79][80]. Furthermore, food insecurity, which is a concern for 24%-46% of surveyed Canadian Arctic households, exacerbates the effects of Cryptosporidium infection on growth and brain development [81]. Important to the context of water treatment in the north, Cryptosporidium is relatively resistant to chlorination; however, boiling, filtration, and UV treatment is effective [77].…”
Section: Cryptosporidiummentioning
confidence: 99%
“…As global trends in fish and wildlife populations continue to decline, vulnerability to food insecurity is exacerbated across many Indigenous communities that rely on fish and wildlife as traditional foods (Elliott et al 2012, Lam et al 2019, Little et al 2021. In Canada, off-reserve First Nation households are nearly four times more likely to be food insecure than non-Indigenous households (Willows et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic diseases such as diabetes are more prevalent in Indigenous Peoples due to diet that has shifted away from traditional foods (Young et al 2000, Damman et al 2008, Hackett et al 2021. Although food insecurity for Indigenous Peoples is a cumulative result of factors that also include a rapid change in lifestyle and often restricted access to healthy foods, many communities experience limited capacity and sovereignty over access and management of traditional foods that have sustained communities for millennia (Hackett et al 2021, Little et al 2021. As challenges relating to levels of food security and access to healthy foods persist, there is growing recognition of the importance of discourse and developing decolonized food and wildlife policies that recognize contemporary Indigenous reliance on traditional foods (Rudolph and McLachlan 2013, Desmarais and Wittman 2014, Grey and Patel 2015, Coté 2016.…”
Section: Introductionmentioning
confidence: 99%